2018
DOI: 10.1002/marc.201800205
|View full text |Cite
|
Sign up to set email alerts
|

Organic Arsenicals as Functional Motifs in Polymer and Biomaterials Science

Abstract: Arsenic (As) exhibits diverse (bio)chemical reactivity and biological activity depending upon its oxidation state. However, this distinctive reactivity has been largely overlooked across many fields owing to concerns regarding the toxicity of arsenic. Recently, a clinical renaissance in the use of arsenicals, including organic arsenicals that are known to be less toxic than inorganic arsenicals, alludes to the possibility of broader acceptance and application in the field of polymer and biomaterials science. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 155 publications
(270 reference statements)
0
7
0
Order By: Relevance
“…For example, the Wilson group has shown that organic arsenicals can be combined with well-defined polymers of controlled molecular weights for oxidation-responsive nanoparticles and hydrogels. 240 242 Cobalt can be used as a metal cross-linking agent with redox responsivity. 243 …”
Section: Redox (Glutathione/ros)mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Wilson group has shown that organic arsenicals can be combined with well-defined polymers of controlled molecular weights for oxidation-responsive nanoparticles and hydrogels. 240 242 Cobalt can be used as a metal cross-linking agent with redox responsivity. 243 …”
Section: Redox (Glutathione/ros)mentioning
confidence: 99%
“…Finally, metal coordination compounds can have interesting redox-responsive behavior, depending on the oxidation state of the metal center. For example, the Wilson group has shown that organic arsenicals can be combined with well-defined polymers of controlled molecular weights for oxidation-responsive nanoparticles and hydrogels. Cobalt can be used as a metal cross-linking agent with redox responsivity …”
Section: Redox (Glutathione/ros)mentioning
confidence: 99%
“…This can also lead to deactivation of the drug as these organoarsenic drugs react readily with blood proteins, in particular transferrin [ 10 ]. In order to limit premature inactivation of the arsenic drugs, a range of nanoparticles have been developed to enhance stability, thus increase activity [ 11 12 ]. These nanoparticles have been decorated with targeting ligands to enhance the accumulation of the drug in cancer tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical renaissance of (in)organic arsenicals, particularly organic arsenicals 4-(N-(Sglutathionylacetyl)amino) phenylarsonous acid (GSAO), [20] 4-(N-(Spenicillaminylacetyl)amino) phenylarsonous acid (PENAO), [21] that contain a common phenylarsonous acid (As(III)) group derived from commercial reagent p-arsanilic acid, has stimulated new interest in the potential of polymeric arsenicals as functional/(re)active platforms for bio(nano)materials design. [22] Over the last 5 years, the vinyl-functionalised organic arsenicals, previously employed in FRP, as well as arsenical-functionalised initiators have been employed for the synthesis of polymeric arsenicals via reversible deactivation radical polymerization (RDRP), furnishing side-chain and end-group functionalized polymeric arsenicals respectively.…”
Section: Introductionmentioning
confidence: 99%